2015
DOI: 10.1063/1.4930876
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced two dimensional electron gas transport characteristics in Al2O3/AlInN/GaN metal-oxide-semiconductor high-electron-mobility transistors on Si substrate

Abstract: The authors report on Al2O3/Al0.85In0.15N/GaN Metal-Oxide-Semiconductor High-Electron-Mobility Transistor (MOS-HEMT) on Si fabricated by using atomic layer deposited Al2O3 as gate insulator and passivation layer. The MOS-HEMT with the gate length of 2 μm exhibits excellent direct-current (dc) characteristics with a drain current maximum of 1270 mA/mm at a gate bias of 3 V and an off-state breakdown voltage of 180 V for a gate-drain spacing of 4 μm. Also, the 1 μm-gate MOS-HEMT shows good radio-frequency (rf) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…We confirmed that the I ds -V ds characteristics were improved by air annealing with a maximum drain current (I max ) of 1140 mA=mm and an on-state resistance (R on ) of 5.3 Ω•mm at a V gs of 2 V. These characteristics are relatively well behaved compared with previous reports. [6][7][8][9][10] After air annealing, we also confirmed the decrease in sheet resistance (R sh ) of around 12% from the results of transmission-line-model (TLM) measurement. Thus, it is likely that the improvements in I max and R on with air annealing can be attributed to the decrease in R sh , probably resulting from the increase in 2DEG density.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…We confirmed that the I ds -V ds characteristics were improved by air annealing with a maximum drain current (I max ) of 1140 mA=mm and an on-state resistance (R on ) of 5.3 Ω•mm at a V gs of 2 V. These characteristics are relatively well behaved compared with previous reports. [6][7][8][9][10] After air annealing, we also confirmed the decrease in sheet resistance (R sh ) of around 12% from the results of transmission-line-model (TLM) measurement. Thus, it is likely that the improvements in I max and R on with air annealing can be attributed to the decrease in R sh , probably resulting from the increase in 2DEG density.…”
supporting
confidence: 71%
“…5) Several methods have been reported to reduce the gate leakage current using metal-oxide-semiconductor (MOS) structures. [6][7][8][9][10] Among the various insulator films that have been used in InAlN=GaN MOS-HEMTs, Al 2 O 3 has been one of the most attractive ones because of its wide band gap (∼7.0 eV), high dielectric constant (∼9.0), and high breakdown voltage (∼10 MV=cm). Furthermore, the Al 2 O 3 films must be kept thin to suppress the degradation of RF performance owing to the decrease in transconductance (g m ).…”
mentioning
confidence: 99%
“…[20] Thus, the atomic-layer-deposited (ALD) Al 2 O 3 is desirable for high-frequency GaN MIS-HEMTs. [21][22][23][24][25][26][27][28] However, InAl(Ga)N/GaN MIS-HEMTs using ALD-Al 2 O 3 suffer from unexpected issues such as a lower drain current than the expected value, a steep decrease in g m when considering the forward gate bias, and severe current collapse, which is a temporary decrease in the drain current under high-power operation. The oxides on the surface of In-based barrier layers (surface-oxide) comprise Al 2 O 3 and indium oxide (In 2 O 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 ] Thus, the atomic‐layer‐deposited (ALD) Al 2 O 3 is desirable for high‐frequency GaN MIS‐HEMTs. [ 21–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, Zhang et al[353] determined the hot-electron relaxation time within lattice-matched InAlN/AlN/GaN heterostructures. The potential for electron device structures was then explored.In 2015, Freedsman et al[354] examined the enhanced two-dimensional electron gas transport characteristics of Al2O3∕AlInN∕GaN metal-oxide-semiconductor high-electron-mobility transistors that were deposited on Si substrates. Also in 2015, Kourdi et al[355] demonstrated that through device optimization and control over the distribution of dopants, it is possible to minimize the side effects associated with InAlN/GaN transistors.…”
mentioning
confidence: 99%